Persepsi Orang Tua terhadap Pembelajaran Daring di Masa Pandemi Covid 19 dari Peningkatan Jumlah Siswa Jenjang Usia Dini di Lembaga Pendidikan Nonformal “Smart Center Indonesia” - Dodi Sutrisno (Bedelau: Journal of Education and Learning, 2021)
The number of Early Age students at the Non-formal Education Institution "Smart Center Indonesia" during the Covid 19 pandemic increased by 58.92%, from this data it raises a big question mark for researchers how is the perception of parents towards online learning during the Covid 19 Pandemic so that the number of students has increased. student enrollment drastically. This study uses a qualitative descriptive method from the results of parental interview data which aims to examine parents' perceptions of online learning during the Covid 19 pandemic from the increase in the number of early age students in non-formal education institutions "Smart Center Indonesia". The result is that from 5 respondents, it was found that the perception of parents who were worried about online learning during the covid 19 pandemic, thus increasing the number of early age students in non-formal education institutions "smart center Indonesia". cannot pass into the best elementary school according to parents, worried that the child will not be able to follow the learning process at the next level, namely the elementary school level. Jumlah siswa jenjang Usia Dini di Lembaga Pendidikan Nonformal “Smart Center Indonesia” selama pandemi Covid 19 mengalami peningkatan sebesar 58,92%, dari data ini menimbulkan tanda tanya besar bagi peneliti bagaimana persepsi orang tua terhadap pembelajaran daring dimasa Pandemik Covid 19 sehingga mengalami peningkatan jumlah pendaftaran siswa secara drastis. Penelitian ini menggunakan metode deskriptif kualitatif dari hasil data wawancara orangtua yang bertujuan meneliti persepsi orang tua terhadap pembelajaran daring dimasa pandemi Covid 19 dari peningkatan jumlah siswa jenjang usia dini di lembaga pendidikan nonformal “Smart Center Indonesia”. Hasilnya terdapat Dari 5 responden didapatkan persepsi orang tua yang khawatir terhadap pembelajaran daring dimasa pandemi covid 19 sehingga meningkatkan jumlah siswa jenjang usia dini di lembaga pendidikan nonformal “smart center indonesia”.Persepsi kekhawatiran itu adalah khawatir terhadap hasil belajar anak yang tidak maksimal, khawatir anak tidak dapat lulus masuk di sekolah dasar yang terbaik menurut orang tua, khawatir anak tidak dapat mengikuti proses pembelajaran dijenjang berikutnya yaitu jenjang sekolah dasar.